Chemical Composition of Faba Bean (Vicia faba L.) Genotypes under Various Water Regimes - Alghamdi, Salem S. (Pakistan Journal of Nutrition, 2009)
A set of thirteen faba bean genotypes were grown at three water regimes (13200, 7600 and 4800 m3/ha) severe, moderate and normal irrigation during the growing season of the crop, to examine the variability of seed chemical composition. The result showed that faba bean genotypes vary greatly in their chemical composition at various water regimes and proximate analysis showed that faba bean genotypes had low moisture contents that ranged from (7.09 - 7.59%). Carbohydrate contents were fairly high (42.4- 47.3%). The highest protein contents under water stress condition and normal irrigation was recorded for Kamlin (36.8 and 39.1%), while the lowest was observed in Sakh1 (35.2 and 37.5%), respectively. Simultaneously, the crude protein content in the seeds varied from 31.8% to 39.7% and consisted of 18 amino acids. Kamlin had the highest (117g/1000g protein) total essential amino acids while Giza402 had the lowest (82.2 g/1000g protein). Methionine and cysteine were the limiting amino acids in the faba seeds. The Protein fraction varied among these genotypes, globulin was followed by glutelin, prolamin and albumin respectively. Evidence was found that protein content increased during water stress treatment.